2013
DOI: 10.1186/2050-2974-1-43
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in anorexia nervosa, bulimia nervosa and eating disorder not-otherwise-specified

Abstract: BackgroundThis study aimed to assess differences in Quality of Life (QoL) across eating disorder (ED) diagnoses, and to examine the relationship of QoL to specific clinical features.Results199 patients with a diagnosed ED completed the Clinical Impairment Assessment (CIA) [Cognitive Behavior Therapy and Eating Disorders, 315–318, 2008] and the Eating Disorders Examination (EDE) [Int J Eat Disord 6:1–8]. Differences between diagnostic groups were examined, as were differences between restrictive and binge-purge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 44 publications
10
45
1
1
Order By: Relevance
“…Individuals with clinical/subclinical eating disorders (EDs) demonstrate markedly impaired quality of life compared to those with low ED psychopathology (DeJong et al, 2013; Hay 2003; Swanson, Crow, Le Grange, Swendsen, & Merikangas, 2011). EDs are highly comorbid with affective disorders such as depression and anxiety (Hudson, Hirpi, Pope, & Kessler, 2007), and impairment in psychosocial functioning tends to persist after treatment even after ED symptoms have remitted (Keel, Mitchell, Miller, Davis, & Crow, 2000; Sullivan, Bulik, Fear, & Pickering, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with clinical/subclinical eating disorders (EDs) demonstrate markedly impaired quality of life compared to those with low ED psychopathology (DeJong et al, 2013; Hay 2003; Swanson, Crow, Le Grange, Swendsen, & Merikangas, 2011). EDs are highly comorbid with affective disorders such as depression and anxiety (Hudson, Hirpi, Pope, & Kessler, 2007), and impairment in psychosocial functioning tends to persist after treatment even after ED symptoms have remitted (Keel, Mitchell, Miller, Davis, & Crow, 2000; Sullivan, Bulik, Fear, & Pickering, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One prominent measure of impairment in EDs (the Clinical Impairment Assessment questionnaire; CIA, specifically aims to address impairment as a result of ED symptoms. The measure has been shown to correlate well with clinician ratings of impairment and degree of symptomatology, providing support that the CIA assesses impairment resulting from an ED (DeJong et al, 2013).…”
mentioning
confidence: 89%
“…As note, EDs "have profound and specific effects on psychosocial functioning" (p. 1105) and a number of studies have described disorderspecific associations with impaired functioning, poor physical health, limitations in daily activities, and psychosocial stressors (e.g., Bamford et al, 2015;Johnson et al, 2001;Striegel-Moore et al, 2003;Wilfley et al, 2003;see Jenkins et al, 2011 for a review). Although there is some uncertainty regarding the specific profiles of impairment across diagnoses (DeJong et al, 2013), impairment has been demonstrated in fullsyndrome and sub-threshold ED diagnoses (e.g., Stice et al, 2013).…”
mentioning
confidence: 99%
“…It also is accompanied by much somatic and psychological comorbidity and results in poor quality of life. 111,112 Positive treatment outcomes are difficult to achieve because the disorder is valued by sufferers. In addition, the anxious and obsessional personality traits with which patients commonly present impede recovery.…”
Section: Introductionmentioning
confidence: 99%